RECOMMENDATIONS OF TEXT MINING-BASED THESIS SUPERVISORS WITH A COMBINATION OF TERM FREQUENCY INVERSE DOCUMENT FREQUENCY AND VECTOR SPACE MODEL - Petti Indrayati Sijabat; Nuraisana Nuraisana (INFOKUM, 2022)
Thesis is a student's scientific paper as one of the requirements to graduate from college, to support the completion of the paper, it involves a supervisor with the main task of ensuring the suitability between the topic and the content outlined in the thesis. Problems in the preparation of the thesis with several phenomena that occur, namely 1) students cannot finish on time according to important dates that have been determined by the Study Program 2) Lecturers do not have sufficient competence on the topics raised by students 3) Determination of Advisory Lecturers is still focuses on the quota that has been provided without ascertaining whether the lecturer in question is able to provide guidance on the topics provided. DestinationThe purpose of this research is to provide recommendations for study programs in determining text mining-based supervisors with a combination of the Tf-Idf algorithm and the Vector Space Model.The urgency of the research is to make it easier for the study program to determine the thesis supervisor so that students can complete the thesis on time because it involves a supervisor who has competence in their field. Astuti, â€œdue to the legal termination of motor vehicle insurance against the insuranced himalaya insurance company in bengkulu cityâ€, jms, vol. 1, no. 01, pp. 1â€“9, jul. 2021. rendi, â€œdetermining factors of mediatorâ€™s success in metro religious courtsâ€, jms, vol. 1, no. 02, pp. 47â€“51, jan. 2022. nurwulandari, â€œanalysis of the influence of roa, der, per, composite stock price index and company size against initial return â€, jms, vol. 1, no. 02, pp. 101â€“115, jan. 2022.